Rancang Bangun Website Profil Sekolah Dengan Desain Responsif Di SD Negeri 1 Penyandingan - Dila Novela; Jumari Iswadi; Eriene Dheanda Absharina (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The development of information technology requires educational institutions to provide information media that are accessible, efficient, and well structured. However, SD Negeri 1 Penyandingan does not yet have an official website, causing information dissemination to rely on manual methods that are less effective. This condition limits access to information for parents and the community. This study aims to design and develop a responsive school profile website using the User-Centered Design (UCD) approach to improve accessibility and the effectiveness of information delivery. The research employed a qualitative and applicative method, with data collected through interviews and observations involving school staff and parents. The UCD stages were applied, including user needs analysis, system design, and implementation. The results indicate that the developed website is able to present school information clearly, systematically, and accessibly across various devices, particularly mobile devices. The website meets user needs and aligns with the context of a rural elementary school environment. This study contributes to strengthening the application of User-Centered Design and responsive web design in the development of educational websites. Future research is recommended to develop more dynamic systems and conduct more comprehensive usability and performance testing.